2017
DOI: 10.1103/physreva.95.063827
|View full text |Cite
|
Sign up to set email alerts
|

Strong spin-orbit interaction of light on the surface of atomically thin crystals

Abstract: The photonic spin Hall effect (SHE) can be regarded as a direct optical analogy of the SHE in electronic systems where a refractive index gradient plays the role of electric potential. However, it has been demonstrated that the effective refractive index fails to adequately explain the lightmatter interaction in atomically thin crystals. In this paper, we examine the spin-orbit interaction on the surface of the freestanding atomically thin crystals. We find that it is not necessary to involve the effective ref… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Cai et al theoretically studied the photon SHE of graphene in the terahertz frequency range and obtained millimeterscale lateral displacements using weak measurement amplification techniques [29]. Similarly, the photon SHE on the surface of atomically thin crystals [30] also achieves a transverse shift value of the order of microns. Luo et al [31] demonstrated that nanoapertures can achieve a giant angular SHE with light and enable full control of the phase gradient at a deepsubwavelength level.…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al theoretically studied the photon SHE of graphene in the terahertz frequency range and obtained millimeterscale lateral displacements using weak measurement amplification techniques [29]. Similarly, the photon SHE on the surface of atomically thin crystals [30] also achieves a transverse shift value of the order of microns. Luo et al [31] demonstrated that nanoapertures can achieve a giant angular SHE with light and enable full control of the phase gradient at a deepsubwavelength level.…”
Section: Introductionmentioning
confidence: 99%
“…The beam shifts on the surface of graphene have been observed via weak measurements [16,17]. In addition, the strong spin-orbit interaction and giant spin-dependent shifts on the surface of graphene have also been predicted [18,19].…”
Section: Introductionmentioning
confidence: 91%
“…To calculate the reflection of an incoming beams plane-polarized in an arbitrary direction, we decompose the incoming field into its p and s components. Sequentially, the four Fresnel's reflection coefficients, r i j for incoming i-polarized and outgoing j-polarized plane waves, are obtained [37][38][39],…”
Section: Topological Phase Transitionsmentioning
confidence: 99%